Hyperlipidaemia treatment and gut microbiology - Zhe, Liu; ChunLi, Yu (Frontiers in Microbiology, 2025)
Numerous studies have shown that hyperlipidaemia is closely related to the gut microbiota, and the study of microbiota in the treatment of hyperlipidaemia is undoubtedly a new target for the treatment and prevention of hyperlipidaemia. The efficacy of regulating the gut microecology and changing the structure of gut flora has been demonstrated by both western and traditional medication, biological therapy, and dietary exercise, so it is particularly important to study the relationship between gut microbiota and the treatment of hyperlipidaemia. In this review, we summarize the mechanism and relationship between the pathogenesis of hyperlipidaemia and gut microbiota, and the mechanism of hyperlipidaemia treatment by influencing the gut microbiota in various treatment modalities, which provides diversified therapeutic ideas and scientific basis for clinical treatment. It also triggers us to think about the relationship between gut microbiota and other diseases, and to explore the influence of gut microbiota is a goal that we still need to explore.